Comparative investigation on the influence of metakaolin, metaillite and steel slag as SCMs in mortar on the corrosion behavior of embedded steel - Achenbach, R.; Raupach, M. (Korose a ochrana materiálu, 2023)
With the aim of saving CO in cement production, various approaches are currently being pursued in the development of new materials. One possibility is to reduce the ratio of clinker to cement by using supplementary cementitious materials (SCMs). Some SCMs like fly ash or granulated blast furnace slag have been used successfully in cement for a long time and their use is covered by standards. Since the availability of these materials cannot be ensured in the long term, alternative additives are also being tested. The results presented here were obtained as part of a joint research project that was carried out in cooperation with the Bauhaus University Weimar. In this study, three different SCMs are investigated with regard to their effect on the corrosion of steel embedded in mortars: A metakaolin, a metaillite, and a modified steel mill slag were each tested at a proportion of 30 wt.% in a CEM I reference cement. In the two-stage tests, the passivation behavior of steel in mortars was first investigated in electrochemical tests. Based on this, tests were carried out in leached solutions of the different binders with different Cl–/OH– ratios. The results show that all the blended types of cement investigated provide passivation of the steel in mortar. The use of the calcined clays metakaolin or metaillite resulted in higher polarization resistances and lower passive current densities as well as increased electrical resistivities, especially for metakaolin. The steel in mortar with the steel mill slag showed comparable electrochemical behavior to the OPC mortar. The tests in leached solutions slightly indicate a higher corrosion-inducing Cl–/OH– ratio when using metakaolin or steel mill slag.